Surface charge switchable and pH-responsive chitosan/polymer core-shell composite nanoparticles for drug delivery application. (15th July 2017) - Huang, W.F.; Tsui, C.P.; Tang, C.Y.; Yang, M.; Gu, Linxia
Abstract: The mutually conflicting surface charge requirements for nanoparticles to have long circulation and good cell affinity have made the development of polymer nanoparticles for controlled drug delivery fall into a dilemma. In order to solve this problem, the first attempt has been made in this work to develop vancomycin loaded composite nanoparticles with a novel chitosan core and poly (lactide- co -glycolide) (PLGA) shell structure and with both pH-responsive and surface charge switchable properties. Spherical composite nanoparticles have been successfully fabricated through a modified emulsion-gelation method with a controllable size (316–573 nm), surface charge (−27.6–31.75 mV) and encapsulation efficiency up to 70.8%. The dilemma can be avoided by tailoring the composite nanoparticles with the specially designed core-shell structure to be negative charged in the beginning and switch to positive charge later on. The negative charge of particles can be switched to positive charge gradually as the erosion of biodegradable polymer shells and exposure of the positive charged chitosan core. The formed chitosan hydrogel exhibited multi-layer structures, which were primarily influenced by chitosan concentration. Influences of the chitosan gelation behaviors on the properties of the composite nanoparticles in response to different chitosan and NH3 concentrations have also been studied. Release rate decreased significantly with increasing chitosan concentration. With the introduction of the chitosan, the increase in drug release rate by orders of magnitude was observed for the samples immersing in the phosphate buffer saline solution of lower pH value proving a pH responsive release property. Drug release profiles of the composite nanoparticles were divided into fast release stage and slow release stage. The fast release stage was well described by a modified first-order kinetic model; while the slow release stage was fitted well with the classical first-order release kinetic model. All the presented results make the proposed composite nanoparticles a promising system for controlled drug delivery.